(untitled) (Homiletic, 2013)
Is today’s Christian preaching really perceived as the living word of God (“viva vox evangelii”) or as boredom, irrelevance and the mere repetition of conventional formula well-known in and outside the Christian community? One hundred years ago Karl Barth and Eduard Thurneysen struggled to find new words for their sermons in order to come closer to what Luther once called the “nova sprach de resurrectione mortuorum.” A century later their question will be asked again against the background of new philosophical insights (“disruption”), liturgical observations (“initiation”), and aesthetic/hermeneutic reflections (“staging/presentation”). A theological description of preaching in the eschatological context of expectation, longing, and astonishment will be suggested.